2013
DOI: 10.1289/ehp.1206244
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals in Tap Water: Human Health Risk Assessment and Proposed Monitoring Framework in China

Abstract: Background: Pharmaceuticals are known to contaminate tap water worldwide, but the relevant human health risks have not been assessed in China.Objectives: We monitored 32 pharmaceuticals in Chinese tap water and evaluated the life-long human health risks of exposure in order to provide information for future prioritization and risk management.Methods: We analyzed samples (n = 113) from 13 cities and compared detected concentrations with existing or newly-derived safety levels for assessing risk quotients (RQs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
89
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(98 citation statements)
references
References 34 publications
7
89
0
2
Order By: Relevance
“…These substances may greatly affect the resistance of bacteria and, consequently, pose a human health risk. A study from China [25] detected several pharmaceuticals in tap water and attempted to assess the human health risk of selected substances based on the U.S. Environmental Protection Agency's (EPA's) Exposure Factors Handbook.…”
Section: Introductionmentioning
confidence: 99%
“…These substances may greatly affect the resistance of bacteria and, consequently, pose a human health risk. A study from China [25] detected several pharmaceuticals in tap water and attempted to assess the human health risk of selected substances based on the U.S. Environmental Protection Agency's (EPA's) Exposure Factors Handbook.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceuticals and their metabolites are becoming increasing ubiquitous in aquatic environments and even in drinking water. These chemicals are introduced as a result of human and animal use, or as residues from manufacturers and hospitals [1][2][3]. The continuous usage and perfusion of these pharmaceutical compounds in water environments may make them "pseudo-persistent," even if they have short half-lives [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Direct relationships between the low levels of pharmaceuticals identified in drinking water and adverse impacts to human health are not being observed at this time [46,47]. However, numerous laboratory studies [48][49][50][51][52][53][54][55][56] and literature reviews [57][58][59] have demonstrated the negative impacts of drugs to aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%